Plotting Spot Wisata Dalam Peta Digital Interaktif Pada Dinas Pariwisata Kota Bengkulu - Yolanda, Helpa; Rizky; Septian R.S., Penti; Satrio Utomo, M. Kholiq; M. Imanullah (Gayaku Publisher, 2024)
This discussion highlights the objectives and functions of agencies related to tourism, the creative economy, and the development of tourism resources in the City of Bengkulu. The Tourism Office has an important role in preparing programs, formulating policies, and implementing government activities. In this context, the active participation of the Tourism Department in creating tourist spot maps and promotion on social media is considered crucial to increasing the success of the project. Solutions to the problem include developing tourist features on the Tourism Department website and using social media by creating post templates on Instagram and Facebook. Through detailed implementation methods, the implementation results of creating spot maps and promotion on social media show a significant increase in information provision, user involvement, and tourist experience in Bengkulu City. Overall, this discussion highlights the role of technology and social media in advancing the city's tourism sector, Bengkulu, providing more accurate information and increasing interaction with tourists.